Propellants of mechanical pruning and plucking of tea (a case of developing countries) - Saeed Firouzi; Fariborz Azarian (Information Processing in Agriculture, 2019)
Tea is one of the most widely consumed natural beverages in the world. High costs of tea pruning and plucking is among the main challenges of its production in Iran as a developing country. Therefore, the development of mechanical pruning and plucking of tea bushes is unavoidable to ensure its sustainable production. In this respect, the present study was carried out in Guilan Province as the leading tea producing region of Iran using Delphi technique in order to identify and analyze the driving factors of the development of tea pruning and plucking mechanization in Iran. After consultation with the academic faculty members in Guilan Province, to form the research panel, 30 experts of tea mechanization were identified and selected from the Tea Organization of Iran, Tea Research Center, and Agriculture Agencies of main tea producing regions of Guilan Province. The results revealed that “Publicizing the benefits of consumption of the domestic tea”, “supporting tea making industries to modernize their systems”, “Reduced prices of domestic and imported mechanical tea equipments by subsidy payment and reduction of tariffs on imports”, “quantitative and qualitative improvement of tea green leaves through applying new agronomic methods and modern irrigation systems”, and “Devoting special bank loans to execute tea mechanization plans” were the most important driving factors of the development of tea pruning and plucking mechanization in Guilan Province as agreed upon by 96.78, 95.89, 95, 95, and 91.42% of panel members, respectively. Thus, recommendations were put forth to help the development of tea pruning and plucking mechanization in Guilan Province. Keywords: Driving factors, Incentives, Agricultural mechanization, Agricultural machinery